2018
DOI: 10.1038/s41389-018-0088-9
|View full text |Cite|
|
Sign up to set email alerts
|

FIBP knockdown attenuates growth and enhances chemotherapy in colorectal cancer via regulating GSK3β-related pathways

Abstract: Colorectal cancer stem cells (CSCs), characterized by self-renewal ability and high expression of proliferative genes, contribute to the chemoresistance of colorectal cancer (CRC). We aimed to identify the molecular mechanisms underlying CRC chemoresistance through comprehensive bioinformatics screenings and experimental confirmation of gene functions. We found that high expression of FGF1 intracellular binding protein (FIBP) was correlated with chemoresistance and poor prognosis in CRC patients. Therefore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…CD44, the transmembrane protein that is the receptor for matrix components such as hyaluronic acid selectin, collagen, and osteopontin, has been proven to help treat acute myeloid leukemia (AML) by inhibiting tumor proliferation, and increasing apoptosis (152, 153). CD133, the glycoprotein also known as prominin-1, is another well-known marker on the CSCs surface and it has been reported to be a useful target in cancers with a large CD133 subpopulation (154, 155). In addition, other drugs approved by FDA are also used for targeting CSC markers such as rituximab (anti-CD20) (156), cetuximab (anti-EGFR) (157159).…”
Section: Therapeutic Strategies Targeting Csc and Their Microenvirementsmentioning
confidence: 99%
“…CD44, the transmembrane protein that is the receptor for matrix components such as hyaluronic acid selectin, collagen, and osteopontin, has been proven to help treat acute myeloid leukemia (AML) by inhibiting tumor proliferation, and increasing apoptosis (152, 153). CD133, the glycoprotein also known as prominin-1, is another well-known marker on the CSCs surface and it has been reported to be a useful target in cancers with a large CD133 subpopulation (154, 155). In addition, other drugs approved by FDA are also used for targeting CSC markers such as rituximab (anti-CD20) (156), cetuximab (anti-EGFR) (157159).…”
Section: Therapeutic Strategies Targeting Csc and Their Microenvirementsmentioning
confidence: 99%
“…In addition, GSK3 functions as an important downstream regulatory switch for numerous signaling pathways involved in the formation of tumors, including the regulation of the Wnt/β-catenin pathway ( 39 , 40 ). In the pathway, activated AKT could bind to the GSK3β complex and then phosphorylate GSK3β at Ser9 and increase the β-catenin levels ( 41 , 42 ) but inhibit GSK3β phosphorylation at Tyr216, also causing the activation of β-catenin ( 43 ). Here, we found that the phosphorylation of GSK3β at Ser9 was downregulated, whereas the phosphorylation of GSK3β at Tyr216 was upregulated in mortalin knockdown cells, which inhibited the phosphorylation of β-catenin at several main sites, such as Ser37, Thr41, and Tyr654.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GSK3 functions as an important downstream regulatory switch for numerous signaling pathways involved in the formation of tumors, including the regulation of Wnt/β-catenin pathway [31,32]. In the pathway, activated AKT could bind to GSK3β complex and then phosphorylate GSK3β at Ser9 and increased the β-catenin levels [33,34], while inhibited GSK3β phosphorylation at Tyr216 also caused the activation of β-catenin [35]. Here, we found the phosphorylation of GSK3β at Ser9 were downregulated while GSK3β at Tyr216 were upregulated in mortalin knockdown cells, which inhibited the phosphorylation of β-catenin at several main sites such as Ser37, Thr41 and Tyr654.…”
Section: Discussionmentioning
confidence: 99%